Resistance training & endurance performance - Schick, F.
Elite and recreational endurance athletes undertake resistance training believing it will improve performance. But training for endurance and training for maximal strength and power represent completely different and opposite forms of activity. Endurance training consists of many thousands of submaximal muscle contractions performed at low to moderate workloads, while training for strength and power involves relatively few contractions at maximal or near maximal force. From a physiological standpoint, it seems unlikely that muscle would be able to adapt to two seemingly incompatible training stimuli when they are undertaken simultaneously. Surprisingly, few good scientific studies have been conducted using well-trained athletes to determine if the improvements in muscular strength gained from resistance training result in enhanced endurance performance.